Efficacy and Safety of Oral Propranolol for Facial Flushing and Erythema of Rosacea Compare to Doxycycline, Sulaimaniyah, Iraq - Karim, Kazhwast Muhammed; Al-Ethawi, Ali Mozan Dahir (Sulaimani Journal for Pure and Applied Sciences, 2023)
Background: Rosacea is an inflammatory skin disease characterized by erythema and flushing, where topical medications are challenging to control and treat. Objectives: To investigate the effect of systemic propranolol/doxycycline in treating facial flushing and erythema in patients with rosacea. Patients and Methods: This randomized control trial study was conducted on 51 patients with rosacea referred to the Sulaimani Dermatology Teaching Center, Sulaimaniyah, Iraq, from October 2021 to August 2022. Among the studied patients, 31 patients were taking oral propranolol, 28 of them did finish the course, while 20 patients were treated with oral doxycycline, 18 of them finished the treatment. Patients have been seen in 5 sessions (12-week treatments), and in each session, the patient's health status, the recovery process of the disease and vital signs have been checked and recorded. Results: The mean age of patients age was 46.65±10.38 years. Most patients were females (65.2%), did not take any drugs (78.4%), did not have a history of illness in the family (82.6%), had skin type 2, and had flushing distribution in the forehead, nose, cheek, and chin. The most common symptom in patients was a burning sensation, followed by a burning and tingling sensation. The most common sign in both groups was erythema. Propranolol positively affected clinical erythema assessment, area, telangiectasia, total erythema score, systolic/diastolic blood pressure and heart rate. Thus, in 5 visits, erythema was significantly reduced in the propranolol group compared to the doxycycline group (p≤0.002). So that after the 5 visits the CAT score was shown that erythema was significantly reduced in the propranolol group compared to the doxycycline group (p≤0.001). Conclusions: Propranolol was more effective than doxycycline in the treatment of rosacea’s flushing and erythema
Keywords: Rosacea; erythema; flushing; propranolol; doxycycline; interventional study